ANALISIS PASAL 1967 KUHPDT TENTANG HAPUSNYA UTANG PIUTANG KARENA DALUWARSA PERSPEKTIF MAQASID AL-SYARIAH - Hasiyah, Hasiyah (ASAS, 2021)
Accounts receivable (Qarḍ) is a loan given to people in need (muqtariḍ) either in the form of money or goods, where the money or goods borrowed must be returned with the same amount. The debt and credit agreement will continue until the muqtarid party pays its debt to the muqriḍ and alms party, where the muqriḍ gives up the debt. Whereas Article 1967 formulates the existence of a period in which the debt and credit agreement can be canceled with the expiration of 30 years, this provision will certainly be detrimental to the muqrid. The problem that will be discussed in this thesis is the analysis of the provisions for the write-off of debts due to expiration which are regulated in article 1967 of the Criminal Code from the perspective of maqasid al-Syari’ah. This research is a library research. The data technique that researchers use is documentation. After the data is collected, the researcher analyzes the descriptive method of qualitative analysis with a thinking approach using the deductive method. The results of the research show that the provisions in article 1967 KUHPdt which explains that debts and receivables can be erased because they have expired or have expired when viewed from the point of view of muqasid syari’ah, have no benefit value and are unable to carry out the interests or objectives of Islamic law which includes 5 main aspects, especially in the storage of assets. Even though debt debt is a muamalah transaction that is synonymous with helping to help but the law is obligatory and very interested in being paid in full, in Islamic law someone who is bound by his debt means that the debt bond will continue to exist until he repays.Keywords: Accounts receivable, Expired, Maqasid al-Syari’ah